Expression of Tenascin in the Uterosacral Ligament is Stronger in Women with Pelvic Organ Prolapse: Tenascin pada Ligamentum Sakrouterina Diekspresikan lebih kuat pada Perempuan dengan Prolaps Organ Panggul - Eny Lusiadewi; Trika Irianta; Efendi Lukas (Indonesian Socety of Obstetrics and Gynecology, 2013)
Objective: This study aimed to compare the expression of tenascin uterosacral ligament in women with and without pelvic organ prolapsen (POP). Methods: The research was carried out in Dr. Wahidin Sudirohusodo Hospital and other educational hospitals of obstetrics and gynecology division UNHAS Faculty of Medicine, which began on January 1st, 2011 until April 2012. This study assessed the expression of tenascin in 35 women with POP levels III and IV, and the controls were 35 women without POP. Tenascin expression was assessed by immunohistochemical examination using tenascin antibody staining (mouse monoclonal antibody Novacastra tenascin C, code NCL-Tenas C). The research was carried out cross sectional. Sampling was done by consecutive sampling. Data processed by the chi-square. The significance level used was 0.05. Results: The results showed that the characteristics of research subjects based on age, education, parity, labor history, history of big babies, not statistically significant. This indicates that the variable does not affect the calculation of the research data. While the characteristics of menopausal status and body mass index (BMI), from the analysis of risk factors for POP is associated significantly with a higher intensity of tenascin in post-menopausal status and BMI> 25 (overweight) (p <0.05). Expression of tenascin in the sample are significantly more powerful, the weak expression (8.6%), moderate (40.0%), and strong (51.4%) than without pelvic organ prolapsed. Expression of tenascin in the control, intensity tenascin weak (77.1%), moderate (20.0%), and strong (2.9%). Conclusion: Expression of tenascin uterosacral ligament was stronger in women with POP compared with a weaker expression of tenascin in women without POP. Keywords: pelvic organ prolapse, risk factors, tenascin